Perception of Physical Education Teachers about the Inclusion of Students with Special Needs (Global Journal of Human-Social Science, 2023)
This systematic review of examines research published from 2012 to 2022 on physical education teachers'perceptions of including students with special needs in physical education classes. The searches yielded (n=665) studies, of which (n=27) were included, the review describes the teachers' perspectives on inclusion, the impostance of inclusive education, the barriers encountered by professionals in daily practice and the need for professional development through basic training or through refresher courses.
Keywords: inclusion; teacher; physical education